Development Of Doe Software For Single-Factor Experiments The Analysis Of Variance Case Of Completely Randomized Design - Zakaria, Muzammer (Universiti Sains Malaysia, 2006)
Design of Experiment (DOE) is a process to study the variables that affecting a certain process. Nowadays, there are not many people know about DOE. From my findings in the internet while studying this subject, I have found that DOE is not only be used in manufacturing field, but also used in many other fields. Since, the scope of applying DOE is becoming wider, it is not impossible if next few years everyone will study about it. As we can see, software about DOE is very few this days, the users always use the statistical software to solve the DOE problems, which is not so relevant or difficult to handle. Therefore, in this project I try to develop DOE software in case of single factor design of experiment. I have used the C++ Builder program to build this software.